An Azobenzene-Bipyridinium Derivative as a Component in the Construction of Photoresponsive Pseudorotaxanes - Andreoni, Leonardo; Cafagno, Dalila; Credi, Alberto; Groppi, Jessica (Synlett, 2025)
We describe the synthesis and characterization of a bipyridinium derivative conjugated with two azobenzene groups (Azo2Bpy2+). The design maintains the ability of the photoswitches to undergo E to Z isomerization upon irradiation to generate a mixture of EE, EZ and ZZ isomers. Moreover, Azo2Bpy2+ is able to undergo self-assembly with dibenzo[24]crown-8 ether to generate [3]-pseudorotaxanes, driven by the strong cooperative effects, for all its geometric isomers.
Keywords: molecular devices; crown ethers; photochemistry; supramolecular chemistry; photoisomerization